(untitled) (TAMADDUN NURI JURNALI, 2024)
This article examines the word-formation capabilities of glosses. The texts of historical novels by Mikhail Sheverdin served as the research material. It was found that several derivatives can be formed on the basis of some units. The most productive unit in this regard was the unit “кишлак”.